Da marginalidade à segregação: contribuições de uma teoria urbana crítica - César Simoni-Santos (El Colegio Mexiquense, A.C., 2017)
Several interpretations of the dynamics of globalization have brought urban issues into the spotlight. Since the conditions of creation of urban society are tied predominantly to extra-regional factors, this process may potentially destroy the local nature of some specific social phenomena and, as a consequence, it calls for a new conceptual framework. This evolution seems to have significantly affected the concept of segregation. In a moment when the world is experiencing a social cleavage that had until recently been a distinguishing mark of Latin America, it is adequate to reconsider the local debate on marginality.